Histodemography of Lymphadenopathy - Majid, Nadira; Talukder, MA Samad; Ali, Syed Mukarram (Delta Medical College Journal, 2013)
Background: Lymph node enlargement presents a clinical problem whose significance can range from trivial to critical, depending on the cause of lymphadenopathy. Diseases involving the lymph node fall primarily into three categories, which include lymphadenitis, metastatic malignancies, malignant lymphoma. It is not feasible to excise every enlarge lymph node. So clinical selection of patients must take place and diagnosis of definite causes of lymphadenopathy by histological examination is essential for appropriate treatment. Objective: The aim was to find the relation and association of proportion of different types of lymphadenopathy with age and gender. Materials and method: This cross sectional study was done in Delta Hospital Limited, Dhaka, Bangladesh during the period of May 2010 to December 2010. A total 88 cases were studied irrespective of age, sex along with clinical diagnosis. Results: Among the study subjects 55.7% was being benign lesions and remaining were with malignant lesions. Among the benign lesions majority (31.8%) were tuberculosis with female predominance which commonly occurs below the age of 20 years, where as non-Hodgkins lymphoma (33.3%) was the commoner form among malignant cases with male predominance occurs in older age group. Mean (±) age of benign and malignant cases was 22.1 (±12.73) years and 44.1 (±17.37) years respectively. Conclusion: The present study revealed that lymphadenopathy occurs more commonly in the middle age group with predominance of benign lesions. Among the benign lesions tuberculosis is the most common one and non-Hodgkins lymphoma is the commonest malignant lesion. DOI: http://dx.doi.org/10.3329/dmcj.v1i1.14969 Delta Med Col J. Jan 2013;1(1):8-12